Impaired kidney function portended a bleak prognosis for surgically treated hypertensive intracerebral hemorrhage patients - Jian Wang; Rui Wang; Hu Qin; Lei Zuo (Annals of Indian Academy of Neurology, 2023)
Purpose: Spontaneous intracerebral hemorrhage (ICH) cases caused by hypertension often have poor prognoses. The use of dehydrant agents, such as mannitol, is common to reduce intracranial pressure and alleviate cerebral edema, but they may also pose a risk of worsening kidney function. This study aimed to investigate the impact of impaired kidney function on the outcomes of surgically treated hypertensive ICH patients. Methods: We conducted a retrospective analysis of a consecutive cohort of patients who underwent surgical intervention due to hypertension-related ICH at our institute between December 1, 2017, and January 31, 2022. Demographic, clinical, radiological, and prognostic data were collected. Patients were categorized into two groups based on 90-day mortality: group A [overall survival (OS) ≤3 months] and group B (OS >3 months). Survival analysis was performed to identify factors associated with poor outcomes. Results: Among the 232 eligible patients, group A exhibited significantly impaired kidney function, as indicated by mean estimated glomerular filtration rate (eGFR) at admission, postoperative, 3-day postoperative, and 7-day postoperative time points (91.9, 82.5, 73.5, 75.2 ml/min/1.73 m2). In contrast, group B did not show significant changes in kidney function (mean eGFR for the corresponding time points: 108.1, 106.5, 111.5, 109.6 ml/min/1.73 m2). The 3-day postoperative eGFR showed the strongest predictive ability for assessing prognosis [areas under the curve (AUC): 0.617, 0.675, 0.737, 0.730]. Univariate and multivariate analyses identified low Glasgow Coma Scale (GCS) score (3–8), ventricle intrusion of hematomas, cardiac failure, larger hematoma volume, infection, and lower 3-day postoperative eGFR as adverse factors for survival. Conclusions: Preserving kidney function is crucial for achieving favorable outcomes in hypertensive ICH cases. Impaired 3-day postoperative eGFR emerged as an independent risk factor for overall survival. Patients with cardiac failure, infection, and larger hematoma volume should receive careful management to improve outcomes.